Handbook of Porous Silicon (Springer International Publishing, 2018)
This handbook updates the most fast-moving research areas of porous silicon research, introduces a range of brand new topics not reviewed before and is even more inclusive of worldwide centres of expertise. Rapid advances are being made in porous silicon anodes for lithium batteries, biodegradable nanoparticles and nanoneedles for medical therapy and imaging, energetics and bio-diagnostic techniques. A number of additional characterization and processing techniques are also reviewed for the first time. Experts from 10 additional countries are involved in the 2nd edition: China, Vietnam, Singapore, Malaysia, Saudi Arabia, Turkey, Netherlands, Switzerland, Belarus, and Brazil, making more than 40 countries in total. The handbook therefore covers expertise from every continent. Another new feature is a review dedicated to industrial activity. This second edition endeavours to provide the community with a truly comprehensive database and up-to-date commentary on this versatile nanostructured material.